Analisis Rekonsiliasi Fiskal Dalam Perhitungan PPh Badan PT. Bali Citra Kinawa Sentosa - Ayu Zovira, Purnamawati Helen Widjaja (Jurnal Paradigma Akuntansi, 2019)
Company prepared financial statement refers to financial accounting standards, where as to meet their tax liabilities the company must undertake fiscal correction on the financial statements in accordance with the tax rules. As for the purpose of this study was to determine whether all revenue or expense which is corrected in accordance with the tax regulations and how much the amount of income tax PT. Bali Citra Kinawa Sentosa in 2017 after the fiscal correction. The method used in this research is descriptive method. Data collected by observation and interview with the company. The result shows that there were some discrepancy made by company in making fiscal financial statement, so that the calculation of corporate income tax becomes incorrect